AUDITORY FUNCTION IN PRETERM INFANTS AT THE AGE OF 3 MONTHS WITH INTRAUTERINE GROWTH RETARDATION AND BORN AT THE GESTATION PERIOD LESS THAN 32 WEEKS - I. V. Rakhmanova; L. G. Sichinava; I. N. D'yakonova; Yu. A. Ledovskikh ("Paediatrician" Publishers LLC, 2013)
The results of auditory function assessment in children with intrauterine growth retardation are analyzed in this study. The audiologic examination with distortion product evoked otoacoustic emission and auditory steady state evoked potentials methods was performed in 49 preterm infants, born at the gestation period less than 32 weeks from the monofetal pregnancy, at the age of 3 months. The observed patients were divided into 2 groups: preterm infants with intrauterine growth retardation (n=25) and preterm infants with body birth-weight appropriate for the gestation period (normotrophic) (n=24). In the group of children with intrauterine growth retardation the amount of patients who did not pass the distortion product evoked otoacoustic emission test was higher than in the group of normotrophic preterm children. The analysis of the results of the auditory steady state evoked potentials in preterm children suggest that there is no reliable hearing impairment in preterm infants with intrauterine growth retardation in comparison with normotrophic age-matched infants. For the objective description of the auditory function in preterm infants with intrauterine growth retardation and normotrophic children born at the gestation period less than 32 weeks at the age of 3 months both afore-mentioned methods should be used.